2018
DOI: 10.1097/rct.0000000000000804
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Source Dual-Energy CT Portal Venous Phase Abdominal CT Scans in Large Body Habitus Patients: Preliminary Observations on Image Quality and Material Decomposition

Abstract: Purpose Our objective was to evaluate image quality (IQ) and material decomposition in patients with large body habitus undergoing portal venous phase abdominal computed tomography (CT) scans on dual-source dual-energy CT (dsDECT) scanners. Methods This retrospective analysis included 30 scans from consecutive patients (19 males/11 females, mean ± SD age = 55.3 ± 17.5 years, range = 27–87 years) with large body habitus (≥90 kg, mean ± SD weight = 105.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Recent versions of DECT platforms and software upgrades have the capability to automate post-processing such that DECT image reconstructions do not hinder workflow (67). Recent studies have shown that single source rapid switching rsDECT suffers from increased beam hardening/streak artifacts on material specific images and patient anatomy can extend outside dual energy field of view (FOV) on dual source scanners (68)(69)(70). However, newer detector-based spectral CT scanners have no limitations on FOV, gantry rotation time or cross-scatter (67).…”
Section: Iterative Reconstruction (Ir)mentioning
confidence: 99%
“…Recent versions of DECT platforms and software upgrades have the capability to automate post-processing such that DECT image reconstructions do not hinder workflow (67). Recent studies have shown that single source rapid switching rsDECT suffers from increased beam hardening/streak artifacts on material specific images and patient anatomy can extend outside dual energy field of view (FOV) on dual source scanners (68)(69)(70). However, newer detector-based spectral CT scanners have no limitations on FOV, gantry rotation time or cross-scatter (67).…”
Section: Iterative Reconstruction (Ir)mentioning
confidence: 99%
“…However, the application of DL image reconstruction in dual-energy CT applications has been limited by insufficient tube output for satisfactory image quality, which can be particularly problematic in obese patients. Rapid-switching single-source dual-energy CT has before now experienced image degradation from photon starvation in material decomposition dual-energy CT in patients >250 lb (113 kg), and larger patient body habitus has necessitated larger gantry bore openings further challenging imaging geometry and contributing to increased streaking and beam hardening artifacts 9–12 …”
mentioning
confidence: 99%
“…Rapid-switching single-source dual-energy CT has before now experienced image degradation from photon starvation in material decomposition dual-energy CT in patients >250 lb (113 kg), and larger patient body habitus has necessitated larger gantry bore openings further challenging imaging geometry and contributing to increased streaking and beam hardening artifacts. [9][10][11][12] A new x-ray tube has recently been developed (Quantix 160; GE Healthcare, Waukesha, WI), which may provide sufficient tube output for DL image reconstruction applications in obese patients. 13 This next-generation x-ray tube platform incorporates a digital cathode, dual flat emitter, wide-view target, and liquid metal bearing that support up to 1300 mA flux at 160 mm of coverage, thereby allowing higher effective flux utilization per unit of time.…”
mentioning
confidence: 99%